History and artificial intelligence: methodology, semantics of machines and decolonial attitude (Tempo e Argumento, 2025)
This article analyzes some of the transformations in historiography in the face of artificial intelligence and the digital society. Initially, it discusses the possible reconfiguration of historical consciousness and the methodological challenges imposed by the advent of digital technologies, questioning whether the historicity of machines can be equated to a certain extent with human experience. Next, the semantics of machines is explored through the metaphor of the “cast away” (used by Rodrigo Bonaldo), which illustrates the constant fallibility involved in the work of historians, programmers, and those who delve into the digital. Finally, the article addresses decoloniality and ethics in digital society, criticizing Eurocentric models in history writing and algorithmic programming. It also advocates the inclusion of decolonial perspectives for critical historiography. Thus, the study invites reflection on how new technologies can reconfigure the understanding of time, memory, and decoloniality in the historical discipline.
Keywords: digital history; artificial intelligence; semantics of machines; decoloniality; digital ethics